2017
DOI: 10.1148/radiol.2016161286
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Breast Percentage Density Estimations from Standard-Dose versus Synthetic Digital Mammograms: Results from a Large Screening Cohort Using Automated Measures

Abstract: Purpose To evaluate agreement between automated estimates of breast density made from standard-dose versus synthetic digital mammograms in a large cohort of women undergoing screening. Materials and Methods This study received institutional review board approval with waiver of consent. A total of 3668 negative (Breast Imaging Reporting and Data System category 1 or 2) digital breast tomosynthesis (DBT) screening examinations consecutively performed over a 4-month period at one institution for which both stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…They found strong correlation for percentage density between s2D and 2D ( r = 0.92), though the more dense the tissue, the more disagreement emerged. Unlike the subjective density assessments in prior two studies above, automated density estimates in this study were 1.7% higher on s2D [ 38 ].…”
Section: Synthesized Mammography Appearancecontrasting
confidence: 65%
“…They found strong correlation for percentage density between s2D and 2D ( r = 0.92), though the more dense the tissue, the more disagreement emerged. Unlike the subjective density assessments in prior two studies above, automated density estimates in this study were 1.7% higher on s2D [ 38 ].…”
Section: Synthesized Mammography Appearancecontrasting
confidence: 65%
“…Compared to radiologists majority score, Quantra TM used on DBT showed comparable inter-observer variability (227). Other algorithms than Quantra TM has been shown to perform comparable breast density estimation in DBT and DM (228,229) and between DM and synthetic DM (230).…”
Section: Automated Breast Density Assessment In Dbtmentioning
confidence: 93%
“…It is not clear whether synthetic mammograms can be reliably used for visual density assessment; one previous study has showed shifts within BI-RADS categories 2–4 when C-View was used in place of FFDM [ 84 ]. The research team from University of Pennsylvania that developed LIBRA software published results from their evaluation of the agreement between automated estimate of breast density from standard and synthesized mammograms [ 85 ]. Briefly, the LIBRA software generates area-based measurements of breast area, dense tissue area, and percentage density from FFDM images.…”
Section: Advantages and Limitations Of Mbd Assessment Methodsmentioning
confidence: 99%